Surgical management of vaginal agenesis using a modified Mc Indoe’s technique: VIMS experience - Tharihalli, Chandrashekhar; V., Muralikrishna; C., Shiva Kumar H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Mullerian agenesis is a challenge to reconstructive surgeons. In order to create a new vagina that mimic the normal one in size, lining and appearance, multiple techniques have been designed; among these techniques Mc Indoe’s vaginoplasty represents the simplest one with good results. Mc Indoe’s operation which involves the creation of a space between bladder and rectum, insertion of a mould covered with split-thickness skin graft into that neo-vaginal space, and use of postoperative vaginal mould for dilation and to avoid stenosis. However, many modifications have been introduced in time in an attempt to increase the success rates. The purpose of vaginal agencies treatment is to create an adequate passage for penetration during sexual intercourse. Methods: Between Jan 2010 to June 2017, ten patients with vaginal agenesis were admitted to Dept of Obstetrics and Gynaecology, VIMS Ballari for vaginal reconstruction. All cases underwent a modified Mc Indoe’s technique, and follow up was done for one year. Results: All ten cases of vaginal agenesis underwent vaginal reconstruction by modified Mc Indoe's technique. Post-operative vaginal length varied from 5 to 7 cm in patients who used mould regularly. Successful skin graft take was achieved in 6 cases. one case of perforation of rectum and one case of vaginal stricture was noted. Conclusions: To optimize sexual comfort, the clinical management of women with vaginal agenesis must be multidisciplinary and individually tailored. Our findings suggest that the modified Mc Indoe’s technique is a simple, effective procedure for the treatment of vaginal agenesis, but proper mould usage after surgery remains the cornerstone of the treatment.